ORGANIZATION OF FINANCIAL ACCOUNTING BASED ON INTERNATIONAL STANDARDS IN THE CONTEXT OF ECONOMIC LIBERALIZATION (International journal of artificial intelligence, 2025)
In the context of economic liberalization, the transition to International Financial Reporting Standards (IFRS) is a critical step toward enhancing the transparency and investment attractiveness of enterprises. This article explores the implementation specifics of IFRS in Uzbekistan, identifies key benefits and challenges, and analyzes both international and local experiences. Particular attention is given to corporate case studies and a cost-benefit analysis of IFRS adoption.